2013
DOI: 10.1037/a0028974
|View full text |Cite
|
Sign up to set email alerts
|

The role of rehearsal on the output order of immediate free recall of short and long lists.

Abstract: Participants tend to initiate immediate free recall (IFR) of short lists of words with the very first word on the list. Three experiments examined whether rehearsal is necessary for this recent finding. In Experiment 1, participants were presented with lists of between 2 and 12 words for IFR at a fast, medium, or slow rate, with and without articulatory suppression (AS). The tendency to initiate output with the first item for short lists (1) did not change greatly when presentation rate was increased from a me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
57
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(68 citation statements)
references
References 107 publications
(331 reference statements)
11
57
0
Order By: Relevance
“…In contrast, although verbal memory performance was greatly reduced by AS, the task remained possible, a result suggesting that verbal rehearsal augmented (but was not strictly necessary) for IFR (a result similar to Grenfell-Essam et al, 2013;and Spurgeon et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In contrast, although verbal memory performance was greatly reduced by AS, the task remained possible, a result suggesting that verbal rehearsal augmented (but was not strictly necessary) for IFR (a result similar to Grenfell-Essam et al, 2013;and Spurgeon et al, 2014).…”
Section: Discussionmentioning
confidence: 96%
“…Rehearsal is often invoked to explain primacy effects within recency-based accounts of IFR (e.g., Tan & Ward, 2000), but Grenfell-Essam, Ward, and Tan (2013) have recently shown that the tendency to initiate recall with the first list item in short lists in IFR was unlikely to be mediated by rehearsal. They showed that doubling the presentation rate from 1 word / s to 2 words / s did not affect the probability of first recall data.…”
Section: Language-specific Explanations Of the Phenomenonmentioning
confidence: 99%
“…Ward et al (2010) argued that this finding may encourage greater theoretical integration between IFR and ISR (as championed by only a small subset of accounts; e.g., Anderson, Bothell, Lebiere, & Matessa, 1998;Brown, Chater & Neath, 2008;Brown, Neath, & Chater, 2007;Farrell, 2012;Grossberg & Pearson, 2008). They also argued that the finding is potentially problematic (without additional assumptions) for those recency-based accounts of IFR that are largely based on data from longer lists and that tend to assume (correctly for longer lists) that the most recent items will be the most highly accessible and most likely to be recalled first (e.g., Brown et al, 2007;Howard & Kahana, 2002;Tan & Ward, 2000;Ward, 2002).…”
mentioning
confidence: 95%
“…Recall is more likely to be initiated with the first word in the list for high frequency words, but towards the end of the list for low frequency words (Sumby, 1963). Grenfell-Essam and colleagues have shown that where recall is initiated has a large effect on primacy and recency (Grenfell-Essam & Ward, 2012Grenfell-Essam et al, 2013, 2017Ward et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The first author's previous work, looking at the recall patterns in two other immediate memory tasks (immediate free recall and immediate serial recall), has shown how important in-depth analysis can be to advance a field (Grenfell-Essam & Ward, 2012Grenfell-Essam, Ward & Tan, 2013, 2017Ward, Tan & Grenfell-Essam, 2010). We hope that a deeper exploration of the recall patterns of controls and dementia cases within the HVLT may help improve its diagnostic efficacy.…”
mentioning
confidence: 98%